Characterization of Naegleria fowleri from two human cases: Insights into its excretion/secretion products - Chacón Camacho, Natalia (2025)
Naegleria fowleri is the etiologic agent of primary acute meningoencephalitis (PAM). This infection is acute, of rapid progression and with high mortality rates. Although this amoeba is commonly found in water and soil, reports of infections do not achieve 500 cases worldwide; problems with diagnosis probably contribute to underestimation. Moreover, information regarding the pathogenicity of this species is still lacking. Costa Rica reported the first three cases of PAM during 2020; from these, two N. fowleri isolates were recovered. The aim of this study was to characterize and compare these isolates, focusing in excretion/secretion products. Analyses of protein profiles by SDS-PAGE and silver staining, protease activity, cytopathic effect over Vero cells and drug susceptibility assays were performed. Proteomic analyses of excretion/secretion products, including extracellular vesicles (EVs), were also assessed. Results obtained were similar for both isolates, especially in protein profiles, cargoes and drug susceptibility. Patterns of multiple bands were observed in each isolate after silver staining. Proteomics analyses revealed a total of 88 and 62 non-redundant proteins as part of the cargo of EVs secreted by trophozoites of N. fowleri Guanacaste and N. fowleri Limón, while conditioned media results revealed 34 and 17 non-redundant proteins, respectively; for these analyses, hydrolase activity and actin filament binding were part of the most represented gene ontology terms in EVs and conditioned media. Regarding drug susceptibility assays, no statistically significant differences were identified between cytotoxic concentration 50 of both isolates with miltefosine or amphotericin B. On the other hand, slight differences in protease profiles and cytopathic effect were found. Although protease activity resulted very similar with substrate buffer at pH 8.5, only N. fowleri Limón showed activity between 40 and 70 kDa at pH 5.0; in contrast, a more rapid cytopathic effect was observed when incubating Vero cells with N. fowleri Guanacaste. Comparative analyses of different N. fowleri isolates, supported by their remarkable genomic heterogeneity that could be reflected in different metabolic repertoires, are key to understanding virulence and pathogenicity of this amoeba, and could help to explain whether different isolates differ in the severity or course of PAM.